2017
DOI: 10.1007/s00439-017-1842-3
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide compound heterozygote analysis highlights alleles associated with adult height in Europeans

Abstract: Adult height is the most widely genetically studied common trait in humans; however, the trait variance explainable by currently known height-associated single nucleotide polymorphisms (SNPs) identified from the previous genome-wide association studies (GWAS) is yet far from complete given the high heritability of this complex trait. To exam if compound heterozygotes (CH) may explain extra height variance, we conducted a genome-wide analysis to screen for CH in association with adult height in 10,631 Dutch Eur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 38 publications
(50 reference statements)
0
12
0
Order By: Relevance
“…As member of different international consortia, we described many new and confirm previously known genes and performed genetic prediction studies for multiple visible traits such as male pattern baldness [167], perceived facial age [168], body height [169], hair color [170], hair structure [171], skin colour [172], eyebrow thickness [173], and eyebrow colour [174].…”
Section: Main Results In the Last 3 Yearsmentioning
confidence: 99%
“…As member of different international consortia, we described many new and confirm previously known genes and performed genetic prediction studies for multiple visible traits such as male pattern baldness [167], perceived facial age [168], body height [169], hair color [170], hair structure [171], skin colour [172], eyebrow thickness [173], and eyebrow colour [174].…”
Section: Main Results In the Last 3 Yearsmentioning
confidence: 99%
“…While much of the research has been conducted on living European populations (88,89), some research has been done with ancient DNA derived from skeletal remains (90). Cox et al (90) observed a decrease in stature between Early Upper Paleolithic and Mesolithic and Neolithic peoples (transition from hunting and gathering subsistence to early farming and herding), but an increase in height between the Neolithic and the Bronze Age (about 5,000 years ago).…”
Section: Genome-wide Association Studies (Gwas)mentioning
confidence: 99%
“…Shared familial environments also can alter the potential to observe signals resulting from gene-environment interactions. Pedigree-based designs allow for the investigation of de novo mutations, parent of-origin effects [96], transmission bias [97], phasing [98,99], and compound heterozygosity [100,101]. Finally, when pedigrees have multiple affected members it is often presumed that the same inherited mutation on a similar genetic background causes the illness in each case.…”
Section: Rare Variants and Pedigreesmentioning
confidence: 99%